P1730 Multimodality assessment of complex ventricular septal defect. (17th January 2020) - Morrison, M L; Kabir, S; Salih, C; Valverde, I; Tometzki, A; Simpson, J M
Abstract: : Case Summary A 16 month old, 8.2 kg patient came forward for evaluation of complex cardiac anatomy with multimodality imaging assessment to ascertain suitability for biventricular repair. A large ventricular septal defect was diagnosed before birth but possible straddling of the tricuspid valve identified postnatally. The patient developed symptoms of congestive cardiac failure and was palliated with a pulmonary artery band. In view of the difficult nature of the defect they were reviewed with 3D-transthoracic echo, transoesophageal echo and cardiac MRI. Their transthoracic echo confirmed situs solitus with levocardia, atrioventricular and ventriculoarterial concordance. There was a well placed pulmonary artery band with peak velocity of 5 m/s. Biventricular systolic function appeared good. There was a large ventricular septal defect at the inlet extending to the muscular septum. There were 2 prominent muscle bundles arising from the ventricular apex and it was difficult to distinguish on echocardiography which of these formed the true ventricular septum (Figures A & B). Although the tricuspid valve opened normally, there were multiple chords extending to overlie the right ventricular aspect of the ventricular septal defect (Figure C), some of which appeared to cross the through defect (*) and attach to the more leftward of the apical trabeculations (Figure D white dotted line illustrates the true plane of ventricular septum which overlies the attachments. Red dotted line represents the plane followed by the leftward apical trabeculation). Cardiac MRI showed that the trabeculation positioned to the left was the true ventricular septum, as it seemed to be in line with the plane of the atrial septum at the crux of the heart (Figure E & F). At surgery her heart was found to be unseptatable due to multiple straddling chords from the tricuspid valve inserting into multiple papillary muscle heads with the left ventricle. Conclusions: The key issue in this case is which of the muscular structures positioned at the ventricular apex is considered to be the true ventricular septum as this determines whether on not there is straddle of the tricuspid valve. In addition the complex and multiple nature of the chordal attachments below the valve made accessing and closing the defect not feasible. Even in the present era with wide availability of advanced, multimodality imaging techniques demonstrating anatomy can still prove challenging in planning surgical repair, especially within the setting of complex congenital heart disease. Many aspects of such cases still only become apparent at the time of surgery and this remains a key issue when counselling parents.